Legal Aspect Setting The Definition Of Terrorism In Law No. 5 Of 2018 Concerning Amendments To Law No. 15 Of 2003 Concerning Eradication Of Criminal Acts Of Terrorism - Bardi, Ahmad (International Journal of Educational Research & Social Sciences, 2023)
Terrorism is a very worrying crime because its development in Indonesia and in other countries is increasing, both in quality and quantity, so that terrorism is not only an Indonesian problem but an international problem. One of the results of changes in the law on combating terrorism in Indonesia is the addition of Article 1 by including restrictions on the qualification of terrorism that were not previously regulated in the law on combating terrorism. This raises its own problems, namely there is no synchronization between the qualification of terrorism and the crime of terrorism, the problem to be examined and analyzed in this study is how the urgency of setting the definition of terrorism in Law No. 5 of 2018 and its comparison with other countries and how the juridical consequences of the inclusion of motives in the definition of terrorism?. The research method used to analyze the problem is to use the normative legal research method with the approach of legislation, concepts and methods of comparison. The results showed that the qualification of terrorism in Law No. 5 of 2018 that terrorism is a crime that depends on a motive, namely ideological, political or security interference motives. It is quite different from the qualification of terrorism in some countries , that other countries that have laws combating the criminal act of terrorism do not regulate the qualification of terrorism and the motives of terrorism, but only regulate the offenses of terrorism and its elements. The regulation of terrorism motives in Law No. 5 of 2018 is ineffective because it is not included as elements of terrorism crimes and even causes multi-interpretations because there is no further explanation of the limits of ideological, political and security interference motives.